Effectiveness of Contextual Learning Models, Problem-Based Learning, and Learning Outcomes - Millah Maryam As-Sa'idah; Ujang Dedih; Maslani Maslani (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2022)
This study aims to determine the effectiveness of contextual, problem-based learning and conventional learning models on student learning outcomes. The method used is quantitative with a comparative design. The object of this research is the learning outcomes of the seventh-grade students of MTs YPPS Sukamiskin. Class VII A consists of 32 students using a contextual model, class VII B has 34 students using a problem-based learning model, and class VII C has 32 students using a conventional one. Testing the data using the one-way ANOVA test which was analyzed by the SPSS version 20 application. The results of the normality test study, data using contextual learning models, problem-based learning and conventional normal distribution, and other evidence are indicated by the distribution of points on the Q-Q diagram on a diagonal line.  While the results of the homogeneity test, the variance data is not homogeneous, this is indicated by the sig value of more than 0.05, namely 0.013. The conclusion from the results of this study is that the use of contextual learning models is more effective than problem-based and contextual learning models. This is evidenced by the average result (mean) using the contextual model is 81.5625, while the average result of the problem based learning model is 61.1765 and the average result of the conventional model is 57.5000.Penelitian ini berujuan untuk mengetahui efektivitas model pembelajaran contextual, problem based learning dan konvensional terhadap hasil belajar siswa. Metode yang digunakan kuantitatif dengan desain komparatif. Objek dalam penelitian ini adalah hasil belajar siswa kelas VII MTs YPPS Sukamiskin. Kelas VII A berjumlah 32 menggunakan model contextual, kelas VII B berjumlah 34 siswa menggunakan model problem-based learning dan kelas VII C berjumlah 32 siswa menggunakan konvensional. Pengujian data menggunakan uji ANOVA satu jalur yang dianalisis oleh aplikasi SPSS versi 20. Hasil penelitian uji normalitas, data yang menggunakan model pembelajaran contextual, problem-based learning dan konvensional berdistibusi normal dan bukti lain ditujukan oleh sebaran titik-titik pada diagram Q-Q berada pada garis diagonal. Sedangkan pada hasil uji homogenitas, data variansi nya tidak homogen hal ini ditujukan oleh nilai sig lebih dari 0,05 yaitu 0,013. Kesimpulan dari hasil penelitian ini adalah penggunaan model pembelajaran contextual lebih efektif dibanding dengan model problem-based learning dan contextual. Hal tersebut dibuktikan hasil rata-rata (mean) dengan penggunaan model contextual adalah 81,5625, sedangkan hasil rata-rata model problem-based learning adalah 61,1765 dan hasil rata-rata model konvensional adalah 57,5000.